2020
DOI: 10.1038/s41598-020-67543-z
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic performances and unnecessary US-FNA rates of various TIRADS after application of equal size thresholds

Abstract: We compared the diagnostic performances and unnecessary fnA rates of several guidelines and modified versions using the size threshold of the ACR TIRADS. Our Institutional Review Board approved this retrospective study and waived the requirement for informed consent and all methods were performed in accordance with the Declaration of Helsinki. A total of 1,384 thyroid nodules in 1,301 patients with definitive cytopathologic findings were included. US categories were assigned according to each guideline. We app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
30
3

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(40 citation statements)
references
References 27 publications
7
30
3
Order By: Relevance
“…As per previous studies relying on the ACR-TIRADS class, FNA would be indicated in a range of 17% to 40%; in this paper, cases with FNA indicated by the ACR system accounted for 46.5% of the nodules, confirming its high “rule-out” role. The ancillary FNA rate was 28.5%, which is significantly lower than the results reported in the literature (63.8%) [ 4 ]. Some limitations of our study should be noted.…”
Section: Discussioncontrasting
confidence: 59%
See 2 more Smart Citations
“…As per previous studies relying on the ACR-TIRADS class, FNA would be indicated in a range of 17% to 40%; in this paper, cases with FNA indicated by the ACR system accounted for 46.5% of the nodules, confirming its high “rule-out” role. The ancillary FNA rate was 28.5%, which is significantly lower than the results reported in the literature (63.8%) [ 4 ]. Some limitations of our study should be noted.…”
Section: Discussioncontrasting
confidence: 59%
“…Although the bioptic procedure is safe with rare complications, the application of TIRADS scores as an ancillary tool may improve the triage with a more efficient clinical management, postponing the performance of FNA in low-risk cases [ 11 , 12 ]. The ACR-TIRADS method was chosen in our study due to its putative superior overall performance [ 4 , 13 , 14 , 15 , 16 ]. Indeed, the other available and widely used US-based evaluation systems (ATA and EU-TIRADS) mainly rely on the assessment of nodules’ features (e.g., shape, margins and echogenicity) without the attribution of a score for each of these characteristics, representing purely pattern-based classifications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various studies have shown the good performance of ACR-TIRADS in selecting thyroid nodules deserving FNA, stressing its high "rule-out" role, as confirmed by our group here and previous experience [1,6,8,[16][17][18]. In the present work, the ACR and EU-TIRADS systems recommended FNA in 46.5% (223/480) and 51.9% (249/480) of the nodules, respectively.…”
Section: Discussionsupporting
confidence: 84%
“…In the international scenario, different alternative ultrasound (US) algorithms have been proposed for characterizing thyroid nodules [1]. The American College of Radiology (ACR) Thyroid Imaging Reporting and Data Systems (TIRADS) consists of a scale with increasing scores for specific US features of thyroid nodules and is able to stratify lesions with a progressively higher risk of malignancy (ROM) [2][3][4].…”
Section: Introductionmentioning
confidence: 99%